The influence of nanocrystallization process on thermal and optical parameter in oxyfluoride glasses - Jaglarz, Janusz; Reben, Manuela (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
The influence of nanocrystallization process in oxyfluoride glasses Na2O–Al2O3–SiO2–LaF3–NaF doped with rare earth (RE) ions on their thermal and optical properties is studied. The thermal characteristics of oxyfluoride glasses (OG) with Tm3+, Yb3+ are presented. The effect of the glass crystallization on thermal stability of the glass and crystallizing phases formed upon heat treatment is investigated by DTA/DSC and XRD methods. It has been found that the effect of nanocrystallization of LaF3 and incorporation of RE elements in formed upon heat treatment nanocrystallites depends on the kind of rare earth elements and is determined by factors of crystallochemical nature and requires adequate proportions between the components forming glass structure.The ellipsometric investigations are performed by M2000 spectroscopic ellipsometer. These measurements allowed us to determine dispersion of refractive indices in the range 190–1700 nm and depolarization coefficients. The influence of nanocrystallization process on refractive indices is discussed.
Optica Applicata, Vol. 40, 2010, nr 2, s. 439-447
Keywords: optyka; oxyfluoride glasses; rare earth elements; athermal and optical properties